Nursing care in post cesarean section due to preeclampsia - Gutierrez-Prieto, Yolanda S.; Cabanillas-Chavez, María Teresa; Morales Garcia, Wilter C. (SCT Proceedings in Interdisciplinary Insights and Innovations, 2024)
Cesarean section is the surgical procedure that consists of the removal of the fetus in a rapid and timely manner that is given as a treatment to the patient with mild pre-eclampsia, to avoid complications such as maternal fetal morbidity and mortality, seizures, postpartum eclampsia, pulmonary edema, cerebrovascular accident, HELLP syndrome, among others. So a human care with quality and warmth was applied contemplating scientific knowledge. The objective is to administer a process of care intervention for a post-cesarean patient due to preeclampsia in the post-anesthetic recovery unit. The study is qualitative, unique clinical case type, which includes a 35-year-old patient, for which the Nursing Care Process was used in its five stages: assessment, diagnosis, planning. Execution and evaluation of the results was done according to the difference of the final and baseline scores respectively. 8 altered patterns were identified and three were prioritized: pattern VI: cognitive-perceptual, pattern VII: self-perception-self-concept, pattern I: perception-health management, critical analysis allowed the identification of 8 diagnoses; being prioritized: acute pain, anxiety and risk of infection, according to the SSPFR format (signs and symptoms, problem and related factor) the evaluation was made according to the difference in final and baseline scores corresponding to +2, +3, +2 .We conclude that according to the problems identified, the nursing care program was administered in its five stages, however, it should be noted that the success of the nursing treatment depends on the timely identification of the problems and adequate treatment.